The Condition of Acidity, Phosphate, And Nitrate in Indonesian Waters - Valdany, Faeza A.; Ihsan, Yudi N; Yuliadi, Lintang PS; Purba, Noir P (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2022)
This research aimed to observe the trend of acidity, nitrate, and phosphate in the Indonesia seas associated with oceanography. Analysis was done by looking at the horizontal condition from main data (acidity, nitrate, and phosphate) and ancillary data (temperature) seasonally in three-layer of depths (0 m, 50 m, and 100 m) for years 2015 using data model of INDESO. The result showed that pattern of acidity, nitrate, and phosphate vary every season. In the upper layer (up to 100 meters), acidity condition ranges from 7.5 to 8, nitrate around 0.01 – 15 mmol N m-3, and phosphate around 0.001 – 1.6 mmol P m-3. The value of acidity is getting lower with depth whereas the nitrate and phosphate values increased with depth. The change in acidity, nitrates and phosphate every season indicates that the monsoon also influences the spread of pH, nitrate and phosphate.Keywords: ocean currents, Indonesia throughflow, sea surface temperature, climate changehate.Â